Use of Palm Oil Waste as Organic Fertilizer to Support Sustainable Environmental Agriculture - Marlina; Anis Tatik Maryani; Elis Kartika; Heri Junedi (Jurnal Prajaiswara, 2023)
This study aimed to examine the proper and sustainable management of palm oil waste to support environmentally sustainable agriculture.ste. For this reason, this study needs to be carried out to provide more general picture of waste utilization innovations. The discussion in this article is about 1) Does palm oil waste have the potential to become an environmental pollutant, 2) What are the advantages of palm oil waste as organic fertilizer in its role as a soil ameliorant, 3) How is palm oil waste managed appropriately and sustainably to overcome environmental pollution. Novelty (optional): Innovation of utilizing palm oil waste by mixing or formulating several wastes. Research Methods: This research used a systematic literature review.Findings/Results: The results showed that 1) Palm oil waste has the potential to become an environmental pollutant, 2) Oil palm waste can be managed as organic fertilizer which has function as a soil ameliorant, 3) Palm oil waste management as organic fertilizer can support environmentally sustainable agriculture. Conclusion: This literature study provides an illustration that palm oil waste has the potential to become an environmental pollutant, thus it must be managed by using appropriate technology in a sustainable manner in treating the waste as organic fertilizer which has function as a soil ameliorant to support environmentally sustainable agriculture